CREATING ELECTRICAL LOAD MAPPING AND DETERMINING THE LOCATION OF THE MAIN REDUCTION SUBSTATION - Qurbonova, Barno; Qurbonov, Abror (Физико-технологического образование, 2024)
In this article reduction of electrical energy waste in the case of the plant’s electricity consumption and in order to improve the efficiency indicator, a cartogram of electrical loads was built and the installation location of the head reducing padstation a was determined